Optimization of Space in the Oyster Mushroom Industry with the Activity Relationship Chart Method - Basuki, Mahmud; Satrio, Pandu Puspo (International Journal of Education, Science, Technology, and Engineering (IJESTE), 2023)
Layout is a technique of arranging facilities to be better than before which aims to minimize all costs and maximize profits. The purpose of this research is to optimize space in XYZ which produces oyster mushrooms. The optimization of space in this study uses the Activity Relationship Chart (ARC) method approach. ARC is a method that identifies the relationship of importance between one facility to another or one activity to another, whether it is important to bring it closer or it should be kept away. The results showed that the layout of the facilities in the XYZ home industry can still be optimized, including adding raw material warehouses, toilets, prayer rooms, ablution places, and the use of vacant land as oyster mushroom houses.